Enzymatic analysis of carbohydrate metabolism in Strongylocentrotus purpuratus larvae during laboratory experiments with different pH treatments - Jasper Hildebrand; Meike Stumpp (PANGAEA, 2025)
Strongylocentrotus purpuratus (Stimpson 1857) originally collected in November 2022 from La Jolla, USA (Lat: 32.842674; Long: -117.257767) were held in flow-through tanks which were filled with water from Kiel Fjord adjusted to 31.5 psu in the Christian-Albrechts-Universität zu Kiel at 10 °C. Carbohydrate-degrading enzymatic activity against various substrates (starch, laminarin, cellulose, xylan, trehalose) was assessed using 3,5-dinitrosalicylic acid (DNS, Miller, 1959). The activities of degradation were quantified by measuring the rate of reducing sugar production resulting from the hydrolysis of soluble starch, carboxymethylcellulose sodium salt (medium viscosity), laminarin from Laminaria digitata, xylan and D-(+)-Trehalose dihydrate under different pHs. For all reactions the amount of reducing sugar was determined spectrophotometrically at 540 nm with glucose as the standard (xylose for xylan characterization).
In: Hildebrand, J; Stumpp, M (2025): Genetic and enzymatic analyses of carbohydrate metabolism in Strongylocentrotus purpuratus larvae [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.968977